2020
DOI: 10.1136/bjsports-2019-101635
|View full text |Cite
|
Sign up to set email alerts
|

How to manage travel fatigue and jet lag in athletes? A systematic review of interventions

Abstract: ObjectivesWe investigated the management of travel fatigue and jet lag in athlete populations by evaluating studies that have applied non-pharmacological interventions (exercise, sleep, light and nutrition), and pharmacological interventions (melatonin, sedatives, stimulants, melatonin analogues, glucocorticoids and antihistamines) following long-haul transmeridian travel-based, or laboratory-based circadian system phase-shifts.DesignSystematic reviewEligibility criteriaRandomised controlled trials (RCTs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 79 publications
0
51
0
1
Order By: Relevance
“…Moreover, sports professionals can encourage athletes to take a YN "nap" instead of traditional ones (using, for example, taped instructions) while taking advantage of travel time (e.g., van Rensburg et al, 2020). Of note, as recovery is a highly individual process, this strategy should be applied according to individual sleep needs and requirements (Loch et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sports professionals can encourage athletes to take a YN "nap" instead of traditional ones (using, for example, taped instructions) while taking advantage of travel time (e.g., van Rensburg et al, 2020). Of note, as recovery is a highly individual process, this strategy should be applied according to individual sleep needs and requirements (Loch et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, because of its effects on sleep latency (Datta et al, 2017;Moszeik et al, 2020), exploring this practice might help athletes with the "sleepability" (the ability to nap on demand) that could be used as a strategic skill to manage sleep challenges and debt (Gupta et al, 2020). These could be due to, for example, travel fatigue and jet lag as athletes are often required to embark on long travel for competition reasons (e.g., van Rensburg et al, 2020). Better sleep would also benefit arousal management; this may reduce stress reactivity, which is caused by the arousal that leaves one overly reactive to stimuli (Park et al, 2020).…”
Section: Yn Effects and Potential Benefits On Athletesmentioning
confidence: 99%
“…Systematic [36,37] and narrative reviews [2,3,21] aimed to summarize the most recent findings and provide practical guidelines on how to best minimize (handle/tackle) the consequences of the air-travel-induced circadian rhythm desynchronization (e.g., jet lag) on various physical performance indicators. Briefly, crossing multiple time zones via air travel and within a limited time frame is instrumental to inducing the loss of synchronicity among the circadian rhythms, thereby affecting sleep, core temperature, gastrointestinal function, and melatonin release, each of which can translate into impaired physical performance in athletes [3].…”
Section: Part Two: Effect Of Long-haul Flights On Physical Performancementioning
confidence: 99%
“…Although the above-mentioned studies have attempted to analyze the effects of long-distance air travel on hydration status, and many studies did evaluate the potential influence of dehydration on physical performance or its associated physiological mechanisms, there is no clear study investigating these effects in a consistent manner. Indeed, the importance of utilizing a proper hydration strategy was recently discussed by van Rensburg et al [36], who examined the effects of jet lag on physical performance in athletes in their systematic review. They looked at a number of factors and concluded that remarkably, there are still no studies looking at the combined effects of hydration status on physical performance of athletes traveling across multiple time zones.…”
Section: Fluid Intakementioning
confidence: 99%
“…Intake of these factors represents a potential intervention for enhancing natural sleep. A number of recent reviews have highlighted the potential for a number of these ingredients to influence sleep and jetlag [16,19]. However, each of these reviews make mention of the need for additional randomised controlled trials, using objective measures of sleep to enhance the quality of research in the area.…”
Section: Introductionmentioning
confidence: 99%